Inflation targeting, between rhetoric and reality: The case of transition economies - Daniel Daianu; Laurian Lungu (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
The paper examines the inflation targeting regime in the context of transition economies. Recent years have witnessed an increasing number of central banks in these countries moving towards the implementation of inflation targeting regimes. However, the success of such a regime depends largely on the degree to which certain general requirements are met. As experience in a number of transition economies has shown so far, targeting inflation is not an easy task. The ongoing restructuring process in these economies makes the inflation forecasting process more difficult and introduces an additional source of uncertainty in the system. By unequivocally choosing inflation as a nominal anchor the central banks could face potential dilemmas if, for example, exchange rate appreciated too much under the pressure of massive capital inflows. The paper presents the broad framework in which inflation targeting could operate efficiently and attempts to assess the extent to which such a regime, when applied to transition economies, could fit into this framework.
Keywords: E52; E60; 330; Inflation Targeting; Eastern Europe; Inflationssteuerung; Systemtransformation; Osteuropa